A Newly Discovered Coin from Kietis Featuring Acheloios Kalykadnos - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Fairly recently, a small bronze coin measuring just 9mm and weighing a mere 0.88g came to market via Bertolami e-Auction 93 (2021), lot 341 (Figure 1), which I will argue dates to the first half of the 4th century BC. On the obverse we find the head of Hermes, who is part of Acheloios’ classical retinue, wearing petasos with head to right, all surrounded by a border of dots. On the reverse we find the forepart of Acheloios (of the Kalykadnos) to right, KIH above, and crescent behind, with points oriented away from Acheloios touching the outer edge of the flan. The coin was tentatively attributed to Kietis by the cataloguing numismatist, and in this essay I’d like to solidify that attribution while discussing the importance of the coin. In my estimation, this coin is particularly noteworthy for two reasons: (1) It is one of the earliest—if not the earliest—attestations of the Kietis region and helps solidify the existence of the ethnic in classical times; and, (2) It is a completely new type in the corpus of Acheloios coins, and the first and only known representation of Acheloios of the Kalykadnos—the largest river of Cilicia, ‘whose mighty stream washes the towers of the city walls.’